Efektivitas Informasi Media Sosial: Survey Pada Informasi Layanan Rumah Sakit di Surakarta - Nur Wahyu Cahyaningsih; Didik Setyawan; Finisha Mahaestri Noor (Media Akuntansi, 2020)
This study aims to examination the effectiveness information conveyed through social media in influencing individual intention to continue use social media to obtain hospital service information. The low response information conveyed by hospital through social media due to minstrust of user perceived not as expected. This study using sampling technique with purposive sampling. Respondents are community user of social media one of hospital in Surakarta. The test result of this study show all hypotheses are supported, except H3 is not supported. These result meaningful that the intention to continue use social media to obtain hospital service information due to high trust toward information formed from expectancy suitability of information obtained from social media.